MENDORONG KETAHANAN KOTA SEMARANG MELALUI PEMETAAN PARTISIPATIF DI KELURAHAN PURWODINATAN - Yogi Andre Yonatan Pakpahan; Artiningsih Artiningsih (Jurnal Riptek, 2018)
Purwodinatan Subdistrict, Semarang City is a study site of the 'Peta Kota' activity held by Hysteria and RNI network. Participatory mapping activities involved the participation of community in Purwodinatan Subdistrict through online and offline mapping. The Peta Kota mapped the physical buildings and public facilities, as well as the village's history and the activities of the residents. Initiative from stakeholder in Peta Kota’s activities provided new knowledge for the community and influences their mindset in improving capacity and building social resilience at Purwodinatan Subdistrict to city resilience at Semarang City. Therefore, the purpose of this study is to identify the external role of the community in promoting social resilience in Purwodinatan Subdistrict by identifying the characteristics of the Peta Kota, the social condition of the village community, the learning process, and the benefits of the Peta Kota process. The method used was qualitative method with in-depth interview as data collection technique. The findings of the study indicate that through networking key in the mapping of Participatory Peta Kota, such as initiation, adaptation, innovation, and relationships can encourage social resilience of the kampung in Purwodinatan Subdistrict.